2014
DOI: 10.1371/journal.pone.0089028
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Maintenance in the Transition to Adolescence: A Longitudinal Study of the Roles of Sport and Lifestyle Activities in British Youth

Abstract: BackgroundPromoting physical activity in youth is important for health, but existing physical activity interventions have had limited success. We aimed to inform intervention design by i) describing drop-out, continuation and uptake of specific activities over the transition to adolescence; and ii) examining Variety (number of different activities/week) and Frequency (number of activity session/week) of activity participation and their associations with changes in objectively measured physical activity from ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
43
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 33 publications
(55 reference statements)
5
43
1
1
Order By: Relevance
“…The longitudinal decline in LPA during the whole day found in our study is consistent with previous research that also revealed a significant age‐related decline in overall objectively measured PA at these ages . However, the decline in both total PA and MVPA during the whole day and in compliance with the recommendations of 60 minutes of MVPA per day observed in the studied child boys and adolescent boys was not statistically significant among girls.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The longitudinal decline in LPA during the whole day found in our study is consistent with previous research that also revealed a significant age‐related decline in overall objectively measured PA at these ages . However, the decline in both total PA and MVPA during the whole day and in compliance with the recommendations of 60 minutes of MVPA per day observed in the studied child boys and adolescent boys was not statistically significant among girls.…”
Section: Discussionsupporting
confidence: 91%
“…However, the decline in both total PA and MVPA during the whole day and in compliance with the recommendations of 60 minutes of MVPA per day observed in the studied child boys and adolescent boys was not statistically significant among girls. Brooke et al noted a MVPA decline in youths from ages 10 to 14 years, which was also notably higher among boys than girls. Several studies also showed a significant MVPA decrease among girls; however, other studies did not find a decrease in MVPA either for boys or for girls .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We know that participation in sport during adolescence is associated with higher physical activity levels in adulthood (Bélanger et al, 2015). However, studies examining sport participation have suggested that sport drop-out (attrition) is relatively high, particularly during adolescence (Olds et al, 2009;Brooke et al, 2014;Eime et al, 2016a). There is evidence that adolescents play fewer sports than in childhood, and many drop out of sport completely (Eime et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%